Selected Topics on Research Challenges in Information Science: Editorial Introduction to Issue 17 of CSIMQ - Benedicte Le Grand; Rebecca Deneckère (Complex Systems Informatics and Modeling Quarterly)
This thematic issue of the Complex Systems Informatics and Modeling Quarterly journal is dedicated to Information Science. It is a selection of the extended best papers presented at the 12th edition of the International IEEE Conference on Research Challenges in Information Science (RCIS’2018). The articles presented in this thematic issue contain at least 30% new material compared to the initial papers. The RCIS conference covers a wide spectrum of topics in the information science field: information search and discovery, requirement engineering, product lines, smart cities and Internet of Things, business processes, recommendation and prediction, security, social computing and Social Network Analysis, Human-Computer Interaction and systems engineering. After an additional reviewing process, the articles which have been finally selected present contributions of different types to the field of information science: models, architectures, frameworks, and surveys.